Editorial : omics and systems approaches to study the biology and applications of lactic acid bacteria - Papadimitriou, Konstantinos (2021)
Early definitions classified lactic acid bacteria (LAB) as Gram-positive, non-sporulating, microaerophilic but aerotolerant, catalase, and oxidase negative bacteria that produce lactic acid. LAB were mostly related to foods as starters, non-starters (NSLAB) and less frequently as spoilers. These definitions necessitated some common evolutionary traits but still remained rather technical and beyond a true evolutionary perspective. For example, diverse bacteria were considered LAB, like members of Bifidobacteriaceae and Lactobacillaceae families, the first belonging to the Actino bacteria and the second to the evolutionarily distant Firmicutes.